Personal Data Legal Protection Policy in Indonesia - Moh Indra Bangsawan; Dewi Kusuma Diarti; Bambang Sukoco (Universitas Muhammadiyah Surakarta, 2023)
The 1945 Constitution of the Republic of Indonesia Article 28 G paragraph (1) emphasizes that every person has the right to personal protection, family, honor, dignity and property under his control, as well as the right to a sense of security and protection from the threat of fear. to do or not do something that is a human right. This research aims to 1). Describe the threat to data resources after the Covid‐19 pandemic 2). Describe the personal data protection policy in Indonesia. This research is normative legal research carried out by examining library materials or secondary data. The approaches used are the statutory approach and the conceptual approach to data resource management. The type of study in this research is more descriptive, because it aims to clearly describe various things related to the object being studied. The policies offered in the research are policies carried out using descriptive analysis. The identification process is carried out by looking for the root causes that influence the lack of optimal legal protection of data resources after the Covid‐19 pandemic.